Evaluasi Utilitas Bangunan Pada GKB UNISSULA - Putro, Adhitio Ekatama; Gunawan, Gunawan; Widihastuti, Ida (Universitas Semarang, 2020)
In the construction of multi-storey buildings, every aspect must be considered in accordance with the rules set out in the Act. Article 7 Paragraph 3 of Law 28/02 states that building construction must meet four aspects, namely safety, health, comfort, and convenience. To support the realization of these aspects, it is necessary to have a building utility. The Joint Lecture Building (GKB) of Sultan Agung Islamic University in Semarang, is a building that has 10 floors and is a busy building because it is used by several faculties, such as the PGSD Faculty, Language Faculty, Communication Faculty, and Nursing Faculty. In the operation of the GKB building, there are several complaints that occur in the GKB such as electricity that often goes out, some rooms have less lighting / dark, queues of elevator users are piling up and visually, the GKB building has the potential of being struck by lightning because it has high above average.Seeing these conditions, the authors conducted a study to evaluate the reliability of buildings based on the utility of the building with methods that have been used in other studies, namely the scoring method that is based on visual inspection and by adding measurement methods, and calculations. From these results found the reliability value of the GKB building on the criterion of health scores got a score of 81, the health and comfort criteria scored 99, the ease criterion scored a score of 98. So the reliability of the GKB building got a score of 92 and was included in the unfit category.